Pola Komunikasi Pendidikan Softskill Berbasis Digital Augmented Reality Terhadap Anak Berkebutuhan Khusus Tunagrahita pada SLBN 02 Makassar - S , Febrianti; Zelfia, Zelfia; Muttaqin Mustari , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
Education of children with special needs is one means to develop the personality and soft skills of children so that they can socialize and adapt to their environment. Children with Special Needs (ABK) are children who experience disturbances or obstacles in their development process. ABK has many types, one of which is mentally retarded children. Children with mental retardation are children who have mental retardation with a low IQ, below the average normal child in general. This research was conducted with the aim of knowing the Communication Pattern of Digital Augmented Reality (AR)-Based Softskill Education for Children with Special Needs Mental Retardation at SLBN 02 Makassar and (2) To find out the form of digital Augmented Reality (AR)-based softskills for Children with Special Needs Mental retardation at SLBN. 02 Makassar using a qualitative approach. Data collection techniques in this study using observation, interviews and documentation. The data obtained were then analyzed by means of data reduction, data display (data display) and drawing conclusions. The results of research at SLBN 02 Makassar show that the Augmented Reality (AR) method is effectively used as a learning method for mentally retarded children in the classroom. The display of 2D and 3D virtual objects can increase students' enthusiasm and motivation to learn. This can improve students' responsiveness in recognizing objects around them and can improve the soft skills of mentally retarded children in communicating.